A comparative study between spiral-filter press and belt press implemented in a cloudy apple juice production process. (15th April 2015) - De Paepe, Domien; Coudijzer, Katleen; Noten, Bart; Valkenborg, Dirk; Servaes, Kelly; De Loose, Marc; Diels, Ludo; Voorspoels, Stefan; Van Droogenbroeck, Bart
Highlights: Comparison between the novel spiral-filter press (SFP) and belt press (BP). A significant higher juice yield with SFP could be obtained. A more turbid juice could be produced with SFP. Enzymatic browning during juice extraction with SFP could be largely avoided. After storage, higher contents of phenolic compounds were observed in SFP juice. Abstract: In this study, advantages and disadvantages of the innovative, low-oxygen spiral-filter press system were studied in comparison with the belt press, commonly applied in small and medium size enterprises for the production of cloudy apple juice. On the basis of equivalent throughput, a higher juice yield could be achieved with spiral-filter press. Also a more turbid juice with a higher content of suspended solids could be produced. The avoidance of enzymatic browning during juice extraction led to an attractive yellowish juice with an elevated phenolic content. Moreover, it was found that juice produced with spiral-filter press demonstrates a higher retention of phenolic compounds during the downstream processing steps and storage. The results demonstrates the advantage of the use of a spiral-filter press in comparison with belt press in the production of a high quality cloudy apple juice rich in phenolic compounds, without the use of oxidation inhibiting additives.